2013
DOI: 10.3174/ajnr.a3435
|View full text |Cite
|
Sign up to set email alerts
|

Automated Posterior Cranial Fossa Volumetry by MRI: Applications to Chiari Malformation Type I

Abstract: BACKGROUND AND PURPOSE Quantification of PCF volume and the degree of PCF crowdedness were found beneficial for differential diagnosis of tonsillar herniation and prediction of surgical outcome in CMI. However, lack of automated methods limits the clinical use of PCF volumetry. An atlas-based method for automated PCF segmentation tailored for CMI is presented. The method performance is assessed in terms of accuracy and spatial overlap with manual segmentation. The degree of association between PCF volumes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 17 publications
1
45
0
Order By: Relevance
“…One case and no control is a major limitation. Recently, morphometric studies have clearly shown significantly smaller volume or underdeveloped bony parts of the PCF in adults [1][2][3]5]. A significant smaller basiocciput in CMI group was demonstrated by Noudel et al [8], but no significant difference was found in the length of the supraocciput and FM.…”
Section: Case Reportmentioning
confidence: 88%
See 3 more Smart Citations
“…One case and no control is a major limitation. Recently, morphometric studies have clearly shown significantly smaller volume or underdeveloped bony parts of the PCF in adults [1][2][3]5]. A significant smaller basiocciput in CMI group was demonstrated by Noudel et al [8], but no significant difference was found in the length of the supraocciput and FM.…”
Section: Case Reportmentioning
confidence: 88%
“…Bagci et al [2] used 9 CMI patients for an atlas-based automated PCF parcellation approach as manually delineated PCF. PCF volumes measured by use of the automated method and with manual delineation were found to be similar, 196.2 ± ± 8.7 vs. 196.9 ± 11.0 cm 3 , respectively.…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…Posterior cranial fossa volumetry was performed by using a previously described automated method. 12 With this method, the PCF, hindbrain, and fourth ventricle volumes were quantified using automated segmentation guided by a CM-I-specific brain atlas. These data provide a measure of hindbrain crowdedness as the ratio of hindbrain/PCF volume.…”
Section: Linear and Volumetric Measurementsmentioning
confidence: 99%